A high-strength polypropylene plastic woven bag and preparation method thereof
Patent Information
- Application Number
- CN202310493055.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-05-05
- Publication Date
- 2025-01-07
- Estimated Expiration
- 2043-05-05
AI Technical Summary
Existing polypropylene woven bags are prone to aging, corrosive, poor antibacterial properties in wind-blown, sun-dried, high-temperature or humid environments, have short service life and environmental pollution problems.
The silver-doped titanium-based organic framework is blended and extruded with polypropylene and polybutylene succinate. After drawing, it is impregnated in a protective impregnate solution to form a surface with self-healing, antibacterial and hydrophobicity. , improve the corrosion resistance and biodegradability of woven bags.
显著提高了聚丙烯塑料编织袋的强度、耐腐蚀性、生物降解性和疏水性,延长了使用寿命,并通过稳定的季铵化银掺杂多孔二氧化钛增强抗菌性能,减少了环境污染。
Smart Images

Figure BDA0004210933910000091 
Figure BDA0004210933910000101
Abstract
Description
Technical Field
[0001] The invention relates to the field of plastic woven bags, in particular to a high-strength polypropylene plastic woven bag and a preparation method thereof. Background Art
[0002] Plastic packaging is widely used in the packaging of food, fertilizers, chemical products and other materials. Plastic woven bags are a type of plastic packaging bags. They are made by extruding, cutting, and unidirectionally stretching the raw materials into flat wires, and then weaving them in warp and weft. Polypropylene is a common raw material for plastic woven bags because it has high impact resistance and high mechanical strength.
[0003] However, most existing polypropylene woven bags have relatively simple performance. When used in wind, sun, high temperature or humid environment, polypropylene woven bags will suffer from aging, corrosion, poor antibacterial properties, low strength and other problems, which will lead to a short service life of polypropylene woven bags. In addition, most polypropylene woven bags are disposable products, and directly discarding them after a large number of uses will cause environmental pollution. Summary of the invention
[0004] The object of the present invention is to provide a high-strength polypropylene plastic woven bag and a preparation method thereof, so as to solve the problems in the prior art.
[0005] In order to solve the above technical problems, the present invention provides the following technical solutions:
[0006] A method for preparing a high-strength polypropylene plastic woven bag comprises the following steps:
[0007] S1: Preparation of silver-doped titanium-based organic frameworks;
[0008] S2: Blending and extruding polypropylene, polybutylene succinate, silver-doped titanium-based organic framework, and sorbitol to obtain a base material;
[0009] S3: Drawing the base material through a wire drawing machine to obtain a flat wire;
[0010] S4: After calcining the silver-doped titanium-based organic framework, the framework is treated with 4-vinylpyridine, 3-bromopropyl-5,5-dimethylhydantoin, and sodium hypochlorite in sequence to prepare quaternary ammonium silver-doped porous titanium dioxide;
[0011] S5: Protective dipping solution is prepared by blending urushiol polyurethane prepolymer, modified bismaleimide and quaternary ammonium silver-doped porous titanium dioxide;
[0012] S6: The flat yarn is immersed in a protective dipping solution, taken out and solidified, dried, woven, cut and sewn to obtain a high-strength polypropylene plastic woven bag.
[0013] Single polypropylene as a raw material for woven bags has poor biodegradability, which is not conducive to environmental protection. In the present invention, polypropylene and polybutylene succinate are blended as the raw material for woven bags, thereby improving the heat resistance and biodegradability of the woven bags. However, there is a compatibility problem between polypropylene and polybutylene succinate. In the present invention, a porous silver-doped titanium-based organic skeleton with high porosity and adjustable pore size is prepared by coordination between terephthalic acid and titanium metal ions. By introducing the silver-doped titanium-based organic skeleton into the base material, the compatibility is improved and the flat wire after drawing has the effect of toughening and antibacterial.
[0014] Furthermore, the preparation of the silver-doped titanium-based organic framework includes the following steps:
[0015] Terephthalic acid, N,N-dimethylformamide and anhydrous methanol are mixed, tetrabutyl titanate is added and transferred to a reaction kettle, kept at 140-150° C. for 22-24 hours, cooled, centrifuged and washed, a mixture of tannic acid and deionized water is added, the pH is adjusted to 7.8-8.2, a silver nitrate aqueous solution is added, and stirred for 1-2 hours to obtain a silver-doped titanium-based skeleton.
[0016] Furthermore, the base material comprises, by weight, 103-112 parts of polypropylene, 10-16 parts of polybutylene succinate, 5-8 parts of silver-doped titanium-based organic framework, and 1-3 parts of sorbitol.
[0017] Furthermore, in step S6, the curing condition is 90-100° C. for 1-2 hours.
[0018] In order to further improve the water resistance of the woven bags and make them still have good antibacterial and corrosion resistance after mechanical damage, the protective impregnation solution is prepared with lacquer phenol polyurethane prepolymer, modified bismaleimide, and quaternary ammonium silver doped porous titanium dioxide. The flat wire is impregnated to form a self-healing water-resistant, corrosion-resistant, and antibacterial surface on the surface of the flat wire, thereby greatly extending the service life of the plastic woven bags.
[0019] Further, the preparation of quaternary ammonium silver-doped porous titanium dioxide comprises the following steps:
[0020] (1) 5,5-dimethylhydantoin, acetone and anhydrous potassium carbonate are mixed, kept warm at 65-70° C. for 1 hour, 1,3-dibromopropane is added and kept warm for 12 hours, and then filtered and distilled under reduced pressure to obtain 3-bromopropyl-5,5-dimethylhydantoin;
[0021] (2) heating the silver-doped titanium-based organic framework to 400° C. at 3° C. / min and keeping the temperature for 5 h to obtain silver-doped porous titanium dioxide; mixing the silver-doped porous titanium dioxide, deionized water, potassium persulfate, and 4-vinylpyridine in a nitrogen atmosphere, stirring for 1-2 h, and washing to obtain modified silver-doped porous titanium dioxide;
[0022] (3) The modified silver-doped porous titanium dioxide, deionized water, and 3-bromopropyl-5,5-dimethylhydantoin are mixed, kept at 85-90° C. for 16-18 hours, cooled, centrifuged, washed, chlorinated with 10% sodium hypochlorite in an ice water bath, washed, and freeze-dried to obtain quaternary ammonium silver-doped porous titanium dioxide.
[0023] In the present invention, a silver-doped titanium-based organic framework is calcined to obtain a stable silver-doped porous titanium dioxide, and then in-situ free radical polymerization and quaternization are used to react with 3-bromopropyl-5,5-dimethylhydantoin and sodium hypochlorite to prepare a multi-grafted quaternized silver-doped porous titanium dioxide, which is added into a protective dipping solution to achieve the effects of antibacterial, water-resistant and corrosion-resistant.
[0024] In order to give the surface of the woven bag excellent self-healing properties so that it can recover quickly after mechanical damage without affecting the antibacterial and corrosion resistance of the woven bag, the prepolymer is prepared by using urushiol, a derivative of catechol with an unsaturated long side carbon chain, and isophorone diisocyanate, furfural amine and 2,2-dithiodiethanol are used as chain extenders, disulfide bonds and furan groups are introduced into the polyurethane, polydimethylsiloxane with low surface energy properties is used as a raw material to synthesize bismaleimide containing polydimethylsiloxane as a curing agent, quaternary ammonium silver doped porous titanium dioxide is used as a toughening agent and an antibacterial agent, and a protective dipping solution is prepared.
[0025] Furthermore, the mass ratio of urushiol polyurethane prepolymer to modified bismaleimide is 2:1; the mass ratio of quaternary ammonium silver doped porous titanium dioxide to the sum of the mass of urushiol polyurethane prepolymer and modified bismaleimide is 3-5%.
[0026] Furthermore, the preparation of urushiol polyurethane prepolymer includes the following steps: mixing urushiol, isophorone diisocyanate, and N,N-dimethylformamide, adding dibutyltin dilaurate, keeping warm at 85-90°C for 1 hour, cooling, adding furfurylamine, 2,2-dithiodiethanol, and N,N-dimethylformamide, and keeping warm at 18-25°C for 3-4 hours to obtain urushiol polyurethane prepolymer.
[0027] Furthermore, the molar ratio of urushiol, furfurylamine and 2,2-dithiodiethanol is 1:1:0.5.
[0028] Furthermore, the preparation of modified bismaleimide includes the following steps: blending bismaleimide, polydimethylsiloxane, and N,N-dimethylformamide, and keeping the mixture at 140° C. for 4-5 hours to obtain modified bismaleimide.
[0029] Beneficial effects of the present invention:
[0030] The invention provides a high-strength polypropylene plastic woven bag and a preparation method thereof. The polypropylene plastic woven bag prepared by the invention has high strength and excellent corrosion resistance, biodegradability, hydrophobicity and self-repairing property.
[0031] A porous silver-doped titanium-based organic framework with high porosity and adjustable pore size is prepared by coordination between terephthalic acid and titanium metal ions. By introducing the silver-doped titanium-based organic framework into the base material, the compatibility of polypropylene and polybutylene succinate blended as raw materials for woven bags is improved, and the flat wire after drawing has toughening and antibacterial effects.
[0032] In order to further improve the water resistance of the woven bags and make them still have good antibacterial and corrosion resistance after mechanical damage, the protective impregnation solution is prepared with lacquer phenol polyurethane prepolymer, modified bismaleimide, and quaternary ammonium silver doped porous titanium dioxide. The flat wire is impregnated to form a self-healing water-resistant, corrosion-resistant, and antibacterial surface on the surface of the flat wire, thereby greatly extending the service life of the plastic woven bags.
[0033] After calcining the silver-doped titanium-based organic framework, a stable silver-doped porous titanium dioxide is obtained, and then in-situ free radical polymerization and quaternization are used to react with 3-bromopropyl-5,5-dimethylhydantoin and sodium hypochlorite to prepare a multi-grafted quaternized silver-doped porous titanium dioxide, which is added to a protective dipping solution to achieve antibacterial, water-resistant and corrosion-resistant effects. Compared with traditional halogen-containing antibacterial agents, it has higher stability; N-halamine is a substance that does not cause environmental pollution and has high biocidal activity. In the present invention, it synergizes with silver-doped porous titanium dioxide to expand the antibacterial range and give the woven bag a wide range of antibacterial properties.
[0034] A prepolymer was prepared using urushiol, a derivative of catechol with an unsaturated long side carbon chain, and isophorone diisocyanate. Furfurylamine and 2,2-dithiodiethanol were used as chain extenders to introduce disulfide bonds and furan groups into polyurethane. Polydimethylsiloxane with low surface energy properties was used as a raw material to synthesize bismaleimide containing polydimethylsiloxane as a curing agent. Quaternary ammonium silver doped porous titanium dioxide was used as a toughening agent and antibacterial agent to prepare a protective dipping solution. After curing, a multiple self-healing network system of furan-maleimide and disulfide-metal containing DA bonds was constructed on the surface of the flat wire, which not only improved the mechanical strength of the woven bag, but also gave the woven bag a water-resistant, corrosion-resistant, hydrophobic and antibacterial surface. The addition of quaternary ammonium silver doped porous titanium dioxide not only had a toughening effect, but also had a significant effect on the hydrophobic properties of the coating, greatly improving the hydrophobicity of the woven bag surface. DETAILED DESCRIPTION
[0035] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0036] It should be noted that if the embodiments of the present invention involve directional indications such as up, down, left, right, front, back, etc., the directional indication is only used to explain a specific posture such as the relative position relationship between the components, the movement status, etc. If the specific posture changes, the directional indication will also change accordingly. In addition, the technical solutions between the various embodiments can be combined with each other, but it must be based on the ability of ordinary technicians in this field to implement. When the combination of technical solutions is contradictory or cannot be implemented, it should be considered that such a combination of technical solutions does not exist and is not within the protection scope required by the present invention.
[0037] The technical solution of the present invention is further described in detail below in conjunction with specific embodiments. It should be understood that the following embodiments are only used to explain the present invention, and are not used to limit the present invention.
[0038] Embodiment 1: A method for preparing a high-strength polypropylene plastic woven bag, comprising the following steps:
[0039] S1: preparing a silver-doped titanium-based organic framework, comprising the following steps:
[0040] 0.75 g of terephthalic acid, 14 mL of N,N-dimethylformamide, and 1.5 mL of anhydrous methanol were mixed, 0.39 mL of tetrabutyl titanate was added and transferred to a reaction kettle, and the mixture was kept at 140° C. for 24 h, cooled, centrifuged, and washed, and a mixture of 0.1 g of tannic acid and 10 mL of deionized water was added, the pH was adjusted to 7.8, 0.55 mL of 0.05 mmol / L silver nitrate aqueous solution was added, and the mixture was stirred for 1 h to obtain a silver-doped titanium-based skeleton;
[0041] S2: Blending and extruding polypropylene, polybutylene succinate, silver-doped titanium-based organic framework, and sorbitol to obtain a base material;
[0042] The composition of the base material is, by weight: 103 parts of polypropylene, 10 parts of polybutylene succinate, 5 parts of silver-doped titanium-based organic framework, and 1 part of sorbitol;
[0043] S3: The base material is drawn through a wire drawing machine to obtain a flat wire with a width of 2 mm;
[0044] S4: Preparation of quaternary ammonium silver-doped porous titanium dioxide, the preparation comprising the following steps:
[0045] (1) 1.6 g of 5,5-dimethylhydantoin, 60 mL of acetone, and 5 g of anhydrous potassium carbonate were mixed, and the mixture was kept at 65° C. for 1 h. 1.4 mL of 1,3-dibromopropane was added and kept warm for 12 h. The mixture was filtered and distilled under reduced pressure to obtain 3-bromopropyl-5,5-dimethylhydantoin.
[0046] (2) heating to 400°C at 2°C / min and keeping the temperature for 5h to obtain silver-doped porous titanium dioxide; in a nitrogen atmosphere, mixing 0.1g of silver-doped porous titanium dioxide, 10mL of deionized water, 0.13g of potassium persulfate, and 0.75mL of 4-vinylpyridine, stirring for 1h, and washing to obtain modified silver-doped porous titanium dioxide;
[0047] (3) 0.1 g of modified silver-doped porous titanium dioxide, 8 mL of deionized water, and 0.05 g of 3-bromopropyl-5,5-dimethylhydantoin were mixed, kept at 85° C. for 18 h, cooled, centrifuged, washed, chlorinated with 10% sodium hypochlorite in an ice water bath, washed, and freeze-dried to obtain quaternary ammonium silver-doped porous titanium dioxide;
[0048] S5: Protective dipping solution is prepared by blending urushiol polyurethane prepolymer, modified bismaleimide and quaternary ammonium silver-doped porous titanium dioxide;
[0049] The mass ratio of urushiol polyurethane prepolymer to modified bismaleimide is 2:1; the mass ratio of quaternary ammonium silver doped porous titanium dioxide to the sum of the mass of urushiol polyurethane prepolymer and modified bismaleimide is 3%;
[0050] The preparation of urushiol polyurethane prepolymer comprises the following steps: 3.16g urushiol, 4.44g isophorone diisocyanate, and 100mL N,N-dimethylformamide are mixed, 20mg dibutyltin dilaurate is added, the mixture is kept warm at 85°C for 1h, cooled, 0.97g furfurylamine, 0.77g 2,2-dithiodiethanol, and 20mL N,N-dimethylformamide are added, the mixture is kept warm at 18°C for 4h, and the urushiol polyurethane prepolymer is obtained;
[0051] The preparation of modified bismaleimide comprises the following steps: 1 g bismaleimide, 0.8 g polydimethylsiloxane and 70 mL N,N-dimethylformamide are mixed and kept at 140° C. for 4 h to obtain modified bismaleimide;
[0052] S6: The flat yarn is immersed in a protective dipping solution, taken out and kept at 90° C. for 2 hours for curing, dried, woven at a warp and weft density of 40 yarns / 100 mm, cut and sewed at the bag mouth, and a high-strength polypropylene plastic woven bag is obtained.
[0053] Embodiment 2: A method for preparing a high-strength polypropylene plastic woven bag, comprising the following steps:
[0054] S1: preparing a silver-doped titanium-based organic framework, comprising the following steps:
[0055] 0.75 g of terephthalic acid, 14 mL of N,N-dimethylformamide, and 1.5 mL of anhydrous methanol were mixed, 0.39 mL of tetrabutyl titanate was added and transferred to a reaction kettle, and the mixture was kept at 140° C. for 24 h, cooled, centrifuged, and washed, and a mixture of 0.1 g of tannic acid and 10 mL of deionized water was added, the pH was adjusted to 8, 0.55 mL of 0.05 mmol / L silver nitrate aqueous solution was added, and the mixture was stirred for 1.5 h to obtain a silver-doped titanium-based skeleton;
[0056] S2: Blending and extruding polypropylene, polybutylene succinate, silver-doped titanium-based organic framework, and sorbitol to obtain a base material;
[0057] The composition of the base material is, by weight: 108 parts of polypropylene, 13 parts of polybutylene succinate, 7 parts of silver-doped titanium-based organic framework, and 2 parts of sorbitol;
[0058] S3: The base material is drawn through a wire drawing machine to obtain a flat wire with a width of 2 mm;
[0059] S4: Preparation of quaternary ammonium silver-doped porous titanium dioxide, the preparation comprising the following steps:
[0060] (1) 1.6 g of 5,5-dimethylhydantoin, 60 mL of acetone, and 5 g of anhydrous potassium carbonate were mixed, and the mixture was kept at 68° C. for 1 h. 1.4 mL of 1,3-dibromopropane was added and kept warm for 12 h. The mixture was filtered and distilled under reduced pressure to obtain 3-bromopropyl-5,5-dimethylhydantoin.
[0061] (2) heating to 400° C. at 2° C. / min and keeping the temperature for 5 h to obtain silver-doped porous titanium dioxide; in a nitrogen atmosphere, mixing 0.1 g of silver-doped porous titanium dioxide, 10 mL of deionized water, 0.13 g of potassium persulfate, and 0.75 mL of 4-vinylpyridine, stirring for 1.5 h, and washing to obtain modified silver-doped porous titanium dioxide;
[0062] (3) 0.1 g of modified silver-doped porous titanium dioxide, 8 mL of deionized water, and 0.05 g of 3-bromopropyl-5,5-dimethylhydantoin were mixed, kept at 88° C. for 17 h, cooled, centrifuged, washed, chlorinated with 10% sodium hypochlorite in an ice water bath, washed, and freeze-dried to obtain quaternary ammonium silver-doped porous titanium dioxide;
[0063] S5: Protective dipping solution is prepared by blending urushiol polyurethane prepolymer, modified bismaleimide and quaternary ammonium silver-doped porous titanium dioxide;
[0064] The mass ratio of urushiol polyurethane prepolymer to modified bismaleimide is 2:1; the mass ratio of quaternary ammonium silver doped porous titanium dioxide to the sum of the mass of urushiol polyurethane prepolymer and modified bismaleimide is 4%;
[0065] The preparation of urushiol polyurethane prepolymer comprises the following steps: 3.16g urushiol, 4.44g isophorone diisocyanate, and 100mL N,N-dimethylformamide are mixed, 20mg dibutyltin dilaurate is added, the mixture is kept warm at 88°C for 1h, cooled, 0.97g furfurylamine, 0.77g 2,2-dithiodiethanol, and 20mL N,N-dimethylformamide are added, the mixture is kept warm at 20°C for 3.5h, and the urushiol polyurethane prepolymer is obtained;
[0066] The preparation of modified bismaleimide comprises the following steps: 1 g bismaleimide, 0.8 g polydimethylsiloxane and 70 mL N,N-dimethylformamide are mixed and kept at 140° C. for 4.5 h to obtain modified bismaleimide;
[0067] S6: The flat yarn is immersed in a protective dipping solution, taken out and kept at 95° C. for 1.5 hours for curing, dried, woven at a warp and weft density of 43 yarns / 100 mm, cut and sewed to obtain a high-strength polypropylene plastic woven bag.
[0068] Embodiment 3: A method for preparing a high-strength polypropylene plastic woven bag, comprising the following steps:
[0069] S1: preparing a silver-doped titanium-based organic framework, comprising the following steps:
[0070] 0.75 g of terephthalic acid, 14 mL of N,N-dimethylformamide, and 1.5 mL of anhydrous methanol were mixed, 0.39 mL of tetrabutyl titanate was added and transferred to a reaction kettle, and the mixture was kept at 150° C. for 22 h, cooled, centrifuged, and washed, and a mixture of 0.1 g of tannic acid and 10 mL of deionized water was added, the pH was adjusted to 8.2, and 0.55 mL of 0.05 mmol / L silver nitrate aqueous solution was added, and the mixture was stirred for 2 h to obtain a silver-doped titanium-based skeleton;
[0071] S2: Blending and extruding polypropylene, polybutylene succinate, silver-doped titanium-based organic framework, and sorbitol to obtain a base material;
[0072] The composition of the base material is, by weight: 112 parts of polypropylene, 16 parts of polybutylene succinate, 8 parts of silver-doped titanium-based organic framework, and 3 parts of sorbitol;
[0073] S3: The base material is drawn through a wire drawing machine to obtain a flat wire with a width of 2 mm;
[0074] S4: Preparation of quaternary ammonium silver-doped porous titanium dioxide, the preparation comprising the following steps:
[0075] (1) 1.6 g of 5,5-dimethylhydantoin, 60 mL of acetone, and 5 g of anhydrous potassium carbonate were mixed, and the mixture was kept at 65-70° C. for 1 h. 1.4 mL of 1,3-dibromopropane was added and kept warm for 12 h. The mixture was filtered and distilled under reduced pressure to obtain 3-bromopropyl-5,5-dimethylhydantoin;
[0076] (2) heating to 400° C. at 2° C. / min and keeping the temperature for 5 h to obtain silver-doped porous titanium dioxide; in a nitrogen atmosphere, mixing 0.1 g of silver-doped porous titanium dioxide, 10 mL of deionized water, 0.13 g of potassium persulfate, and 0.75 mL of 4-vinylpyridine, stirring for 2 h, and washing to obtain modified silver-doped porous titanium dioxide;
[0077] (3) 0.1 g of modified silver-doped porous titanium dioxide, 8 mL of deionized water, and 0.05 g of 3-bromopropyl-5,5-dimethylhydantoin were mixed, kept at 90° C. for 16 h, cooled, centrifuged, washed, chlorinated with 10% sodium hypochlorite in an ice water bath, washed, and freeze-dried to obtain quaternary ammonium silver-doped porous titanium dioxide;
[0078] S5: Protective dipping solution is prepared by blending urushiol polyurethane prepolymer, modified bismaleimide and quaternary ammonium silver-doped porous titanium dioxide;
[0079] The mass ratio of urushiol polyurethane prepolymer to modified bismaleimide is 2:1; the mass ratio of quaternary ammonium silver doped porous titanium dioxide to the sum of the mass of urushiol polyurethane prepolymer and modified bismaleimide is 5%;
[0080] The preparation of urushiol polyurethane prepolymer comprises the following steps: 3.16g urushiol, 4.44g isophorone diisocyanate, and 100mL N,N-dimethylformamide are mixed, 20mg dibutyltin dilaurate is added, the mixture is kept warm at 90°C for 1h, cooled, 0.97g furfurylamine, 0.77g 2,2-dithiodiethanol, and 20mL N,N-dimethylformamide are added, the mixture is kept warm at 25°C for 3h, and the urushiol polyurethane prepolymer is obtained;
[0081] The preparation of modified bismaleimide comprises the following steps: 1 g bismaleimide, 0.8 g polydimethylsiloxane and 70 mL N,N-dimethylformamide are mixed and kept at 140° C. for 5 h to obtain modified bismaleimide;
[0082] S6: The flat yarn is immersed in a protective dipping solution, taken out and kept at 100° C. for 1 hour for curing, dried, woven at a warp and weft density of 45 yarns / 100 mm, cut and sewed at the bag mouth, and a high-strength polypropylene plastic woven bag is obtained.
[0083] Comparative Example 1: Example 3 was used as the control group, in which no silver-doped titanium-based organic framework was added to the base material, and other processes were normal.
[0084] Comparative Example 2: Taking Example 3 as the control group, silver-doped porous titanium dioxide was used to replace quaternary ammonium silver-doped porous titanium dioxide, and other processes were normal.
[0085] Comparative Example 3: Taking Example 3 as the control group, titanium dioxide was used to replace the quaternary ammonium silver-doped porous titanium dioxide, and the other processes were normal.
[0086] Comparative Example 4: Example 3 was used as the control group, 2,2-dithiodiethanol was not added, and other processes were normal.
[0087] Comparative Example 5: Example 3 was used as the control group, furfurylamine was not added, and other processes were normal.
[0088] Comparative Example 6: Taking Example 3 as the control group, the ratio of the mass of quaternary ammonium silver-doped porous titanium dioxide to the sum of the mass of urushiol polyurethane prepolymer and modified bismaleimide was 2.9%, and the other processes were normal.
[0089] Comparative Example 7: Taking Example 3 as the control group, the ratio of the mass of quaternary ammonium silver-doped porous titanium dioxide to the sum of the mass of urushiol polyurethane prepolymer and modified bismaleimide was 5.1%, and the other processes were normal.
[0090] Comparative Example 8: Example 3 was used as the control group, no protective dipping solution was prepared, and other processes were normal.
[0091] In the embodiment and the comparative example, the thickness of the flat yarn is 500 μm, the thickness of the protective layer formed on the flat yarn by the protective dipping solution is 250 μm, and the thickness of the woven bag is 1 mm.
[0092] Source of raw materials:
[0093] Polypropylene C600HF: Dongguan Jinshixiang Plastic Raw Materials Co., Ltd.; Polybutylene succinate (AR): (Alpha) Zhengzhou Alpha Chemical Co., Ltd.; Terephthalic acid P108506, N,N-dimethylformamide D111999, dibutyltin dilaurate D100274, tetrabutyl titanate T104104, tannic acid T305809, 5,5-dimethylhydantoin D137034, 4-vinylpyridine V105595, isophorone Diisocyanate I109582, furfurylamine F111778, polydimethylsiloxane H431357: Aladdin reagent; urushiol 83258-37-1: Sichuan Weikeqi Biotechnology Co., Ltd.; 2,2'-dithiodiethanol 380474, bismaleimide 803561, sorbitol C0494: Merck reagent; methanol, silver nitrate, potassium carbonate, acetone, 1,3-dibromopropane, potassium persulfate, sodium hypochlorite, analytical grade: Sinopharm Group reagent.
[0094] Performance Test:
[0095] Tensile strength: Tested according to GB / T1040.1-2006, temperature 25℃, cut into 100mm long, 10mm wide, 1mm thick, tensile speed 500mm / min, each sample was tested 5 times to get the average value;
[0096] Water contact angle: Hydrophobicity is characterized by water contact angle, which is tested by leaving 4 μL of deionized water for 3 seconds;
[0097] Characterization of self-repair rate: scratch the protective layer with a length of 500 μm and a depth of 180 μm, place it in a 60°C oven for 6 hours, observe it with an optical microscope, and record the repair rate;
[0098] Antibacterial activity: Gram-negative bacteria Escherichia coli were selected for testing, and the number of viable bacteria was determined by plate culture method;
[0099] Corrosion resistance characterization: soak the sample in 10% dilute sulfuric acid solution and observe after 15 days. If the sample does not bubble or break, it is qualified. The results are shown in the following table;
[0100]
[0101]
[0102] The invention provides a high-strength polypropylene plastic woven bag and a preparation method thereof. The polypropylene plastic woven bag prepared by the invention has high strength and excellent corrosion resistance, biodegradability, hydrophobicity and self-repairing property.
[0103] By comparing Example 3 with Comparative Example 1, it can be seen that a porous silver-doped titanium-based organic skeleton with high porosity and adjustable pore size is prepared by coordination between terephthalic acid and titanium metal ions, and by introducing a silver-doped titanium-based organic skeleton into the base material, while improving the compatibility of polypropylene and polybutylene succinate blended as raw materials for woven bags, the flat wire after drawing has a toughening and antibacterial effect.
[0104] By comparing Example 3 with Comparative Example 2 and Comparative Example 3, it can be seen that in the present invention, the silver-doped titanium-based organic framework is calcined to obtain a stable silver-doped porous titanium dioxide, and then in-situ free radical polymerization and quaternization are used to react with 3-bromopropyl-5,5-dimethylhydantoin and sodium hypochlorite to prepare a multi-grafted quaternized silver-doped porous titanium dioxide, which is added to the protective dipping solution to achieve antibacterial, water-resistant and corrosion-resistant effects. Compared with traditional halogen-containing antibacterial agents, it has higher stability; N-halamine is a substance that does not cause environmental pollution and has high biocidal activity. In the present invention, it synergizes with silver-doped porous titanium dioxide to expand the antibacterial range and give the woven bag a wide antibacterial property; the addition of quaternized silver-doped porous titanium dioxide not only has a toughening effect, but also has a significant effect on the hydrophobicity of the coating, greatly improving the hydrophobicity of the surface of the woven bag.
[0105] By comparing Example 3 with Comparative Example 4 and Comparative Example 5, it can be seen that in order to give the woven bag surface excellent self-healing properties, the present invention uses lacquer phenol, a derivative of catechol with an unsaturated long side carbon chain, and isophorone diisocyanate to prepare a prepolymer, furfural amine and 2,2-dithiodiethanol are used as chain extenders, disulfide bonds and furan groups are introduced into the polyurethane, and polydimethylsiloxane with low surface energy properties is used as a raw material to synthesize bismaleimide containing polydimethylsiloxane as a curing agent, quaternary ammonium silver doped porous titanium dioxide is used as a toughening agent and antibacterial agent to prepare a protective dipping solution, and after curing, a multiple self-healing network system of furan-maleimide and disulfide-metal containing DA bonds is constructed on the surface of the flat wire, which improves the mechanical strength of the woven bag while giving the woven bag a water-resistant, corrosion-resistant, hydrophobic and antibacterial surface.
[0106] By comparing Example 3 with Comparative Examples 6 and 7, it can be seen that the ratio of the mass of quaternary ammonium silver-doped porous titanium dioxide to the sum of the mass of urushiol polyurethane prepolymer and modified bismaleimide is 3-5%, which can effectively improve various properties of the film.
[0107] By comparing Example 3 with Comparative Example 8, it can be seen that in order to further improve the water resistance of the woven bag and make the woven bag still have good antibacterial and corrosion resistance after suffering mechanical damage, lacquer phenol polyurethane prepolymer, modified bismaleimide, and quaternary ammonium silver doped porous titanium dioxide are used to prepare a protective dipping solution, and the flat wire is impregnated to form a water-resistant, corrosion-resistant, and antibacterial surface with self-healing properties on the surface of the flat wire, thereby greatly extending the service life of the plastic woven bag.
[0108] The above descriptions are only embodiments of the present invention and are not intended to limit the patent scope of the present invention. All equivalent structural changes made using the present invention specification under the inventive concept of the present invention, or direct / indirect applications in other related technical fields, are included in the patent protection scope of the present invention.
Claims
1. A method for preparing a high-strength polypropylene plastic woven bag, characterized in that: The following steps are involved: S1: Preparation of silver-doped titanium-based organic frameworks; S2: Blending and extruding polypropylene, polybutylene succinate, silver-doped titanium-based organic framework, and sorbitol to obtain a base material; S3: Drawing the base material through a wire drawing machine to obtain a flat wire; S4: After calcining the silver-doped titanium-based organic framework, the framework is treated with 4-vinylpyridine, 3-bromopropyl-5,5-dimethylhydantoin, and sodium hypochlorite in sequence to prepare quaternary ammonium silver-doped porous titanium dioxide; S5: Protective dipping solution is prepared by blending urushiol polyurethane prepolymer, modified bismaleimide and quaternary ammonium silver-doped porous titanium dioxide; S6: dipping the flat yarn in a protective dipping solution, taking it out and curing it, drying it, weaving, cutting it, and sewing the bag mouth to obtain a high-strength polypropylene plastic woven bag; The preparation of silver-doped titanium-based organic framework includes the following steps: Terephthalic acid, N,N-dimethylformamide and anhydrous methanol are mixed, tetrabutyl titanate is added and transferred to a reaction kettle, the mixture is kept at 140-150° C. for 22-24 hours, cooled, centrifuged and washed, a mixture of tannic acid and deionized water is added, the pH is adjusted to 7.8-8.2, a silver nitrate aqueous solution is added, and the mixture is stirred for 1-2 hours to obtain a silver-doped titanium-based organic framework; The preparation of quaternary ammonium silver doped porous titanium dioxide comprises the following steps: (1) Mix 5,5-dimethylhydantoin, acetone and anhydrous potassium carbonate, keep the mixture at 65-70°C for 1 hour, add 1,3-dibromopropane and keep the mixture at this temperature for 12 hours, filter and distill under reduced pressure to obtain 3-bromopropyl-5,5-dimethylhydantoin; (2) heating the silver-doped titanium-based organic framework to 400°C at 3°C / min and keeping the temperature for 5 hours to obtain silver-doped porous titanium dioxide; mixing the silver-doped porous titanium dioxide, deionized water, potassium persulfate, and 4-vinylpyridine in a nitrogen atmosphere, stirring for 1-2 hours, and washing to obtain modified silver-doped porous titanium dioxide; (3) The modified silver-doped porous titanium dioxide, deionized water, and 3-bromopropyl-5,5-dimethylhydantoin are mixed, kept at 85-90° C. for 16-18 hours, cooled, centrifuged, washed, chlorinated with 10% sodium hypochlorite in an ice water bath, washed, and freeze-dried to obtain quaternary ammonium silver-doped porous titanium dioxide.
2. The method for preparing a high-strength polypropylene plastic woven bag according to claim 1, characterized in that: The curing condition in step S6 is 90-100° C. for 1-2 hours.
3. The method for preparing a high-strength polypropylene plastic woven bag according to claim 1, characterized in that: Calculated by weight, the base material comprises: 103-112 parts of polypropylene, 10-16 parts of polybutylene succinate, 5-8 parts of silver-doped titanium-based organic framework, and 1-3 parts of sorbitol.
4. The method for preparing a high-strength polypropylene plastic woven bag according to claim 1, characterized in that: The mass ratio of urushiol polyurethane prepolymer to modified bismaleimide is 2:
1.
5. The method for preparing a high-strength polypropylene plastic woven bag according to claim 1, characterized in that: The preparation of urushiol polyurethane prepolymer includes the following steps: mixing urushiol, isophorone diisocyanate and N,N-dimethylformamide, adding dibutyltin dilaurate, keeping warm at 85-90°C for 1 hour, cooling, adding furfurylamine, 2,2-dithiodiethanol and N,N-dimethylformamide, keeping warm at 18-25°C for 3-4 hours, and obtaining urushiol polyurethane prepolymer.
6. The method for preparing a high-strength polypropylene plastic woven bag according to claim 5, characterized in that: The molar ratio of urushiol, furfurylamine and 2,2-dithiodiethanol is 1:1:0.
5.
7. The method for preparing a high-strength polypropylene plastic woven bag according to claim 1, characterized in that: The preparation of modified bismaleimide comprises the following steps: Bismaleimide, polydimethylsiloxane and N,N-dimethylformamide are mixed and kept at 140° C. for 4-5 hours to obtain modified bismaleimide.
8. A high-strength polypropylene plastic woven bag, characterized in that: Prepared according to the preparation method according to any one of claims 1 to 7.
Citation Information
Patent Citations
High-strength antibacterial plastic and preparation method thereof
CN112920445A
Environment-friendly plastic woven bag production process
CN115874455A